Effects of Enteromyxum spp. (Myxozoa) infection in the regulation of intestinal E‐cadherin: Turbot against gilthead sea bream - Ronza, Paolo; Estensoro, Itziar; Bermúdez Pose, Roberto; Losada García, Ana Paula; Pérez Cordón, Gregorio; Gómez Pardo, María Belén; Sitjà Bobadilla, Ariadna; Quiroga Berdeal, María Isabel (Journal of Fish Diseases)
This is the peer reviewed version of the following article: Ronza, P, Estensoro, I, Bermúdez, R, et al. Effects of Enteromyxum spp. (Myxozoa) infection in the regulation of intestinal E‐cadherin: Turbot against gilthead sea bream. J Fish Dis. 2020; 43: 337– 346, which has been published in final form at https://doi.org/10.1111/jfd.13130. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions Enteromyxoses are relevant diseases for turbot and gilthead sea bream aquaculture. The myxozoan parasites invade the intestinal mucosa, causing a cachectic syndrome associated with intestinal barrier alteration; nonetheless, their pathological impact is different. Turbot infected by Enteromyxum scophthalmi develop more severe intestinal lesions, reaching mortality rates of 100%, whereas in E. leei‐infected gilthead sea bream, the disease progresses slowly, and mortality rates are lower. The mechanisms underlying the different pathogenesis are still unclear. We studied the distribution and expression changes of E‐cadherin, a highly conserved protein of the adherens junctions, in the intestine of both species by immunohistochemistry and quantitative PCR, using the same immunohistochemical protocol and common primers. The regular immunostaining pattern observed in control fish turned into markedly irregular in parasitized turbot, showing an intense immunoreaction at the host–parasite interface. Nevertheless, E‐cadherin gene expression was not significantly modulated in this species. On the contrary, no evident changes in the protein distribution were noticed in gilthead sea bream, whereas a significant gene downregulation occurred in advanced infection. The results contribute to the understanding of the different host–parasite interactions in enteromyxoses. Host and parasite cells appear to establish diverse relationships in these species, which could underlie the different pathological picture This work has been funded by the Spanish Ministry of ...